Sustainability indicators : measuring the immeasurable. - Bell, Simon, 1957-; Morse, Stephen, ....- (London : Earthscan, 2008)
Widely considered to be a foundation text in the crucial task of doing sustainability, this revised and fully updated edition of Sustainability Indicators continues to address this vital dimension. Building on the groundbreaking first edition, the authors bring the indicator literature up to date and show that the basic requirement for a systemic approach is now well-grounded in experiential evidence. They examine the origins and development of the Systemic Sustainability Analysis (SSA), which as been developed in practice in a number of countries on an array of projects since the first edition. They also look at how SSA has evolved into Systemic Prospective Sustainability Analysis (SPSA) and now into IMAGINE, and they provide an assessment of the strengths and weaknesses of projects which undertake work in the general field of sustainable development and in particular how a wide range of participatory methodologies have been adopted.
Keywords: Duurzaamheid; Systemic Sustainability Analysis